2019
DOI: 10.1007/s10096-019-03680-2
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular rapid diagnostic tests for Toxoplasma infection in humans and animals

Abstract: Infection by Toxoplasma gondii is prevalent worldwide. The parasite can infect a broad spectrum of vertebrate hosts, but infection of fetuses and immunocompromised patients is of particular concern. Easy-to-perform, robust, and highly sensitive and specific methods to detect Toxoplasma infection are important for the treatment and management of patients. Rapid diagnostic methods that do not sacrifice the accuracy of the assay and give reproducible results in a short time are highly desirable. In this context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 128 publications
(153 reference statements)
3
31
0
2
Order By: Relevance
“…The prevalence recorded in this study is based on a molecular method and is higher than those previously reported in small ruminants of Iran: 37.5% (sheep) and 22.7% (goat) in southwest Iran (Asgari et al, 2011), 34.32 % (sheep) in south of Iran (Armand et al, 2016), and 56.66% (sheep) and 44.16 (goat) in Eastern Iran (Tavakoli-Kareshk et al, 2017). This prevalence could reflect the LAMP is 10-1000 times more sensitive compared with conventional nested PCR (Khan and Noordin, 2019;Kong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence recorded in this study is based on a molecular method and is higher than those previously reported in small ruminants of Iran: 37.5% (sheep) and 22.7% (goat) in southwest Iran (Asgari et al, 2011), 34.32 % (sheep) in south of Iran (Armand et al, 2016), and 56.66% (sheep) and 44.16 (goat) in Eastern Iran (Tavakoli-Kareshk et al, 2017). This prevalence could reflect the LAMP is 10-1000 times more sensitive compared with conventional nested PCR (Khan and Noordin, 2019;Kong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of serological methods including indirect fluorescent antibody tests, enzyme-linked immunosorbent assay, immunosorbent agglutination assay, indirect hemagglutination assay, modified agglutination test, Sabin-Feldman dye test, and Western blot have been applied in extensive epidemiological surveys (Dard et al, 2016). Although serological tests are used extensively in epidemiologic studies, because they are time-consuming, lack in diagnosing primary infections, present antigen cross-reactivity, and antibodies disappear in the long-term, these tests are not reliable when compared to molecular techniques (Sun et al, 2017 for direct detection of T. gondii DNA in tissues (Khan and Noordin, 2019). The first PCR assay for the detection of T. gondii was founded based on the amplification of the 35-repeat B1 gene of the T. gondii genome (Burg et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serological methods play a major role in the diagnosis of T. gondii infection in humans and animals [4,5]. Several serological tests have been developed using either live tachyzoites or native soluble antigens; however, they are expensive, laborious, and nonspeci c [6].…”
Section: Introductionmentioning
confidence: 99%
“…Serological methods play a major role in the diagnosis of T. gondii infection in humans and animals [5,6]. Several serological tests have been developed using either live tachyzoites or native soluble antigens; however, they are expensive, laborious, and nonspeci c [7].…”
Section: Introductionmentioning
confidence: 99%